Beginning Ubuntu for Windows and Mac users : start your journey into free and open source software - Haines, Nathan (Apress, 2023)
Completely updated for this exciting third edition, Beginning Ubuntu for Windows and Mac Users will help you start your journey into Free and Open Source Software with Ubuntu 22.04.1 LTS with GNOME 42. This book is a friendly guide to installing and running Ubuntu for people who are already efficient and happy with Windows or macOS computers. It teachers new Ubuntu users how to navigate their new operating system, perform basic tasks and suggests specific applications to handle routine tasks. You'll start by installing Ubuntu and its related "flavors" (Kubuntu, Ubuntu MATE, etc.) and how they differ from each other. The rest of the book breaks down application suggestions by broad categories to fill in gaps in the default installed system, or suggest fun things that the reader might not have even thought of. The command line is handled after you are comfortable with the system and ready for something interesting but different. It's presented as a powerful interface that can either be approached casually as a unique method of interacting with the computer, as an occasional tool to use, or as a fun way to get in touch with an early way of using a computer. A brief look at "power user" topics gives advice on managing running processes, installing alternate desktop software, using virtual desktops and creating virtual machines. It's a great way to round off the book with starting points for advanced topics that are more specialty topics. An appendix describes the Ubuntu release schedule, naming, and timing. The book is designed to function as a "travel guide" to Ubuntu, offering both a scenic tour through some of the great software in Ubuntu in a practical "here's what you can do with this" style as well as a comprehensive reference guide that the reader can return to over and over to learn how to accomplish specific tasks.